2015
DOI: 10.1177/1090198115590781
|View full text |Cite
|
Sign up to set email alerts
|

A Process Evaluation of the Alaska Native Colorectal Cancer Family Outreach Program

Abstract: This article presents the results of a process evaluation of the Alaska Native (AN) Colorectal Cancer (CRC) Family Outreach Program, which encourages CRC screening among AN first-degree relatives (i.e., parents, siblings, adult children; hereafter referred to as relatives) of CRC patients. Among AN people incidence and death rates from CRC are the highest of any ethnic/racial group in the United States. Relatives of CRC patients are at increased risk; however, CRC can be prevented and detected early through sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 26 publications
0
16
0
Order By: Relevance
“…All mixed methods studies used congruent triangulation [72–85], except for one that chose a sequential transformative design [86]. Qualitative studies included four case studies [8790], and the methods of data collection used were interviews [9092], focus groups [89, 93] or open-ended questions [88]. The number of participants ranged from 6 [41] to 5963 [43] participants.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…All mixed methods studies used congruent triangulation [72–85], except for one that chose a sequential transformative design [86]. Qualitative studies included four case studies [8790], and the methods of data collection used were interviews [9092], focus groups [89, 93] or open-ended questions [88]. The number of participants ranged from 6 [41] to 5963 [43] participants.…”
Section: Resultsmentioning
confidence: 99%
“…The number of participants ranged from 6 [41] to 5963 [43] participants. Twenty-nine studies focused on one ethnic group [27, 30–36, 39, 41, 42, 4749, 51, 57, 69, 75, 77–80, 8285, 87, 89, 92] while thirty-three included more than one ethnic group [28, 29, 37, 38, 40, 4346, 50, 5256, 5868, 70–73, 86, 91, 93] and five studies did not report the ethnicity of their participants [74, 76, 81, 88, 90].…”
Section: Resultsmentioning
confidence: 99%
“…‘I've seen this many, many times in the Indian Health Service and now in the Alaska Native Health System is that when the grant for a program starts to shrink, the program also begins to shrink. And when the grant goes away, the program goes away and it has nothing to do with how important that program is to the health of the population or how successful the program is,’ (key informant for an Alaskan Native cancer outreach programme) 34 …”
Section: Resultsmentioning
confidence: 99%
“…In a similar study by Jean-Jacques et al (14), 23% of participants had incorrect or nonfunctional telephone numbers. Lasser et al (15) reported that of those eligible for patient navigation, 25% could not be contacted after 8 to 11 telephone call attempts. When a tribal facility or health system chooses to use CHRs to assist with cancer screening, CHRs need to have designated time to focus on this task.…”
Section: Discussionmentioning
confidence: 99%
“…When a tribal facility or health system chooses to use CHRs to assist with cancer screening, CHRs need to have designated time to focus on this task. Patient navigators hired in 1 facility in Alaska specifically to assist with CRC screening efforts dramatically increased the number of CRC patients’ first-degree relatives who completed screening ( 16 ). Future studies could seek to determine how much outreach is appropriate before reaching saturation.…”
Section: Discussionmentioning
confidence: 99%